MANAJEMEN PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI HALAQOH DI SDIT HARAPAN BUNDA PURWOKERTO - Widi Puspita, Aprilia (CV. Amerta Media, 2018)
The management of the religious character of the students through the halaqoh program is one of the efforts encompassed the goals of national education in the form of religious students. The purpose of this research is to know about the planning, organizing, actuating, and controlling program of religious character building of students through halaqoh program. This research uses descriptive method with qualitative approach, and interview. Subjects in this study were the head of madrasah and head of halaqoh program and staff of the halaqoh murabbi in SDIT Harapan Bunda. The results showed that: 1) Planning the halaqoh method and character formation of the RPP which refers to the existing syllabus. The targets to be achieved match the student's progress. 2) Organizing is done through the division of tasks and responsibilities of the murabbies. 3) Implementation and actuating of the program carried out every day with methods and references on the RPP that has been made. 4) And supervision/evaluation is done through performance evaluation at the end of the school year.Key Words: Religious Character, Halaqoh Method, SDIT Harapan Bunda Purwokerto